The Theocentric Theology of Peter Taylor Forsyth - Miller, Ridley Paul (My University, 1995)
The British Congregationalist theologian Peter Taylor Forsyth (1848-1921) attempted to formulate a consciously theocentric theology during the height of Protestant liberalism. He did so in opposition to the two traditions which, he believed, contributed to the liberal outlook -- rationalism which stressed the autonomy of reason and was manifested in the rise of historical criticism)and romanticism which stressed the autonomy of subjective feeling and was prevalent in popular piety. Both these tendencies were anthropocentric. They took as their point of departure human religious aspirations rather than the sovereignty and holiness of God.
Holiness is the central category in Forsyth's theology. It defines the other concepts such as grace, redemption and reconciliation. Forsyth attempted to understand holiness in terms relevant to peculiar conditions of modern consciousness. He did so primarily by dealing with Christian experience as the encounter between the two personalities and wills -- the holy will of God and the sinful human will.
Forsyth responded to what he considered to be the illegitimate claims of historical method by developing a dogmatic method. This method, in turn, was applied to the major problem raised by historical consciousness, namely, the person and nature of Jesus Christ. Christology, according to Forsyth's method, is centred on the atoning work of Christ, not on the historical Jesus.
At the same time, Forsyth considered experience indispensable. He attempted to define experience theocentrically as the result of the encounter with the holiness and grace of God, not of a "religious a priori."
Forsyth's theology suffers from conceptual confusion at several key points, especially in his Christology. However, he has made an important contribution to contemporary Christian thought by reorienting theology towards the objective holiness of God. By providing an alternative to liberalism on the one hand and Protestant orthodoxy on the other, he anticipated many of the issues that preoccupied Protestant thought following the First World War.
Keywords: Religion; Religion